Environmental & architectural phenomenology. Vol. 31, issue 2 - (:unkn) unknown (Kansas State University. Architecture Department, 2020)
Besides “Place and COVID-19,” “Items of interest,” and “citations received,” this issue includes the following items: An “in memoriam” for architect and sacred geometer Keith Critchlow, who died in London in April; A “book note” on philosopher Dermot Moran’s study, Husserl’s Crisis of the European Sciences and Transcendental Phenomenology (2010); A “book note” on philosopher Ingrid Leman Stefanovic’s The Wonder of Water (2020), an edited collection examining how human experience relates to decisions about water; Torontonian Robert Fabian’s update on downtown neighborhood planning in his city (“A New Urban Place”); Philosopher John Russon’s exploration of the lived ambiguity of travelling to a foreign place (“The Border at the Heart of Human Life”); Independent researcher Stephen Wood’s discussion of two contrasting modes of science teaching—what he calls “knowledge-based learning” vs. “understanding-based learning” (“An Understanding-Grounded Approach to Science Education”)’; Science educator Henri Bortoft’s explication of Goethe’s proto-phenomenology of nature as one example of a science of wholeness (originally published as four separate essays in the last four EAP issues and now integrated into one) (“Seeing and Understanding Holistically: Goethean Science and the Wholeness of Nature”).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals